The diagnosis and treatment of early pulmonary tuberculosis in children - Coward, N. A. (The University of Edinburgh, 1913)
Recent investigations, conducted both in. the post mortem room and by means of the various Tuberculin .tests on.the living make it apparent.that Tuberculosis in Children, is a much commoner form of disease, and occurs at an earlier age,.than was formerly. imagined.

In conclusion we would urge the vital necessity for early diagnosis in this.insidious disease, and the need of utilising every possible means of establishing the same. When the signs are definite, the symptoms well marked, it is often too late for hope of any permanent cure, . the case is now no longer early, but advanced. It is in the early stages that we must look to combat the disease with any degree of success.

Tuberculin as a means of diagnosis may be of use, but it is a. two edged sword, and the danger of lighting up quiescent fool is too real to be lightly disregarded. In.the words of Sir Clifford Allbutt: there is too much at stake; and even for, the expert the number of 'normals' (or persons practically normal) who react is embarrassing In the stage preceding the presence of physical signs, we must look for slight irregularity of temperature - a sub- normal temperature in the morning is suspicious, 98.5 at that hour is too high and even more suspicious (Clifford Allbutt and most characteristic, one with a swing from 97°-99° at night. A feeling of.tiredness, general malnutrition, poor chest development and expansion, with deficient air entry, all these go,towards establishing an affirmative diagnosis. A positive von Pirquet's reaction - with certain reservations -'and, on X raying, a restricted movement of the diaphragm on one or other side, or shadows round. the roots of the lungs are confirmatory; while a family history of phthisis or exposure to infection must give additional weight to the evidence. The opsofic Index in skilled hands may afford valuable information.

The earliest physical sign of value is the continued presence of crepitations, brought out often only by coughing. When expectoration is present the presence of Tubercle bacilli makes the diagnosis certain.

With regard to treatment, we shall increase the patient's resistance by an open air life, by a diet With a due proportion of proteid and fat, the latter added to by cod liver oil, and by.the exhibition of creosote. We shall regulate his auto-innoculation by rest, coupled with graduated exercises and labour, and in suitable cases by the use of Tuberculin. The exercises should aid in improving the general musculature,.the chest expansion and development and.the air entry.

Preventitive treatment consists in removing the child from debilitating: conditions, and surroundings, in his avoidance of chills and colds, and in attending to his teeth, throat, bowels and other organs and functions, so that a high standard of health may be reached and maintained.